Influence of atmospheric pressure plasma process parameters on the mechanical behavior of thermoplastic joints. (October 2020) - Moroni, F.; Musiari, F.; Sciancalepore, C.; Messori, M.
Abstract: The capability of the Atmospheric Pressure Plasma Treatment (APPT) to increase the shear strength of adhesively bonded Single Lap Joints (SLJ) realized with polymeric adherends was investigated, by exploring the different response obtainable by changing the surface-to-nozzle distance and the treatment speed and by considering an industrial application as target. Beyond APPT, abrasion and chemical treatments were also performed and considered as reference. Three thermoplastic resins were used as adherends: polypropylene (PP), polyethylene (PE) and polyamide 66 (PA66). In addition to the mechanical characterization, even the variation of the surface free energy associated with the different combinations of parameters employed for the APPT was evaluated by means of optical contact angle (OCA) measurements. Moreover, for some representative combinations of substrates and APPT parameters, the changes of the polymer chemical structure were assessed by means of infra-red spectroscopy (IR). Finally, the sensitivity of the mechanical behavior to the time between the treatment and the deposition of the adhesive was assessed. The results showed that, in a plasma treated joint, a decrease of the surface-to-nozzle distance assured however an increase of the shear strength with respect to the chemical treated samples, provided that the treatment speed was correspondingly risen up. The trend of the wettability with the process configuration appeared to be consistent with the one exhibited by the joint shear strength, while any apparent influence of the delay time was detectable within 24 h, which allowed to assume that APPT represents a reliable pre-treatment technique for industrial applications.